Transversal competences in inicial teacher training: the case of leisure. - M. Isabel Luis Rico; Tamara De La Torre Cruz; M. Camino Escolar Llamazares; Jonathan Huelmo García; Carmen Palmero Cámara; Alfredo Jiménez Eguizábal (INFAD, 2017)
Our research focuses on determining the preeminence of education for leisure within the competencial configuration of teachers in their initial training through the analysis of international, European, and national documents related to profesional teaching skills. The interest lies in the detected need to include within teaching performance aspects related to transversal skills, that may satisfy the educational objective of promoting and developing each student.